Impact of salmon farming in the antibiotic resistance and structure of marine bacterial communities from surface seawater of a northern Patagonian area of Chile - Javiera Ortiz-Severín; Christian Hodar; Camila Stuardo; Constanza Aguado-Norese; Felipe Maza; Mauricio González; Verónica Cambiazo (Biological Research)
Abstract Background Aquaculture and salmon farming can cause environmental problems due to the pollution of the surrounding waters with nutrients, solid wastes and chemicals, such as antibiotics, which are used for disease control in the aquaculture facilities. Increasing antibiotic resistance in human-impacted environments, such as coastal waters with aquaculture activity, is linked to the widespread use of antibiotics, even at sub-lethal concentrations. In Chile, the world's second largest producer of salmon, aquaculture is considered the primary source of antibiotics residues in the coastal waters of northern Patagonia. Here, we evaluated whether the structure and diversity of marine bacterial community, the richness of antibiotic resistance bacteria and the frequency of antibiotic resistance genes increase in communities from the surface seawater of an area with salmon farming activities, in comparison with communities from an area without major anthropogenic disturbance. Results The taxonomic structure of bacterial community was significantly different between areas with and without aquaculture production. Growth of the culturable fraction under controlled laboratory conditions showed that, in comparison with the undisturbed area, the bacterial community from salmon farms displayed a higher frequency of colonies resistant to the antibiotics used by the salmon industry. A higher adaptation to antibiotics was revealed by a greater proportion of multi-resistant bacteria isolated from the surface seawater of the salmon farming area. Furthermore, metagenomics data revealed a significant higher abundance of antibiotic resistant genes conferring resistance to 11 antibiotic families in the community from salmon farms, indicating that the proportion of bacteria carrying the resistance determinants was overall higher in salmon farms than in the undisturbed site. Conclusions Our results revealed an association between bacterial communities and antibiotic resistance from surface seawater of a coastal area of Chile. Although the total bacterial community may appear comparable between sites, the cultivation technique allowed to expose a higher prevalence of antibiotic resistant bacteria in the salmon farming area. Moreover, we demonstrated that metagenomics (culture-independent) and phenotypic (culture-dependent) methods are complementary to evaluate the bacterial communities’ risk for antibiotic resistance, and that a human—influenced environment (such as salmon farms) can potentiate bacteria to adapt to environmental stresses, such as antibiotics.